In Situ Sprayed Biotherapeutic Gel Containing Stable Microbial Communities for Efficient Anti‐Infection Treatment - Yan, Jian‐Hua; Zheng, Di‐Wei; Gu, Hui‐Yun; Yu, Yun‐Jian; Zeng, Jin‐Yue; Chen, Qi‐Wen; Yu, Ai‐Xi; Zhang, Xian‐Zheng (Advanced science, 2023)
Systematic administration of antibiotics to treat infections often leads to the rapid evolution and spread of multidrug‐resistant bacteria. Here, an in situ‐formed biotherapeutic gel that controls multidrug‐resistant bacterial infections and accelerates wound healing is reported. This biotherapeutic gel is constructed by incorporating stable microbial communities (kombucha) capable of producing antimicrobial substances and organic acids into thermosensitive Pluronic F127 (polyethylene‐polypropylene glycol) solutions. Furthermore, it is found that the stable microbial communities‐based biotherapeutic gel possesses a broad antimicrobial spectrum and strong antibacterial effects in diverse pathogenic bacteria‐derived xenograft infection models, as well as in patient‐derived multidrug‐resistant bacterial xenograft infection models. The biotherapeutic gel system considerably outperforms the commercial broad‐spectrum antibacterial gel (0.1% polyaminopropyl biguanide) in pathogen removal and infected wound healing. Collectively, this biotherapeutic strategy of exploiting stable symbiotic consortiums to repel pathogens provides a paradigm for developing efficient antibacterial biomaterials and overcomes the failure of antibiotics to treat multidrug‐resistant bacterial infections. In situ sprayed biotherapeutic gel containing stable microbial communities is constructed to control multidrug‐resistant bacterial infections and accelerate wound healing. The active antimicrobial substances and organic acids secreted by the microbial community have remarkable abilities to self‐stabilize and antagonize exogenous pathogens, while avoiding bacteria‐induced systemic inflammation.